Influence of poxidochemicals on enzyme systems of liver mitochondria membranes in pregnant rats - Tuychieva Dilfuza; Alimova Rano; Mirkhamidova Parida (BIO Web of Conferences)
Considerable experimental material has been accumulated on the influence of various abiotic environmental factors and various chemicals on the activity of some enzymes and multienzyme systems of mitochondria. Studying the effect of pesticides or defoliants on the functioning of the mitochondrial respiratory chain is one of the most important tests used to decipher the primary mechanisms of intoxication in the body. A study of the state of the enzyme systems of liver mitochondrial membranes of pregnant rats and embryos shows that poisoning with defoliants - butylcaptax and dropp - reduces the activities of NAD.H oxidase, succinate oxidase and cytochrome c oxidase at all stages of pregnancy and embryonic development. The NAD.H-oxidase activity of mitochondria of pregnant rats and embryos was found to be most strongly inhibited by butylcaptax poisoning. Butylcaptax leads to a deeper inhibition of the rate of electron transfer in various fragments of the respiratory chain of liver mitochondria of pregnant rats and their embryos. The most profound inhibition is observed in the NAD.H oxidase pathway in case of butylcaptax poisoning on the 19th day of pregnancy